2003
DOI: 10.1097/00002030-200309050-00006
|View full text |Cite
|
Sign up to set email alerts
|

Persistent immune activation in HIV-1 infection is associated with progression to AIDS

Abstract: Increased T cell activation has predictive value for HIV-1 disease progression even before seroconversion. These data support the hypothesis that persistent hyperactivation of the immune system may lead to erosion of the naive T cell pool and CD4 T cell depletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
529
0
21

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 666 publications
(577 citation statements)
references
References 30 publications
18
529
0
21
Order By: Relevance
“…5), even though there is a correlation between immune activation and viral load (r=0.443) as seen in other studies [6,11,14]. This suggests a relationship between IL-7Ra expression levels and immune activation that is independent of viral load.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…5), even though there is a correlation between immune activation and viral load (r=0.443) as seen in other studies [6,11,14]. This suggests a relationship between IL-7Ra expression levels and immune activation that is independent of viral load.…”
Section: Discussionsupporting
confidence: 57%
“…Although many correlates have been identified that may influence the rate of HIV progression, including immune activation, and the disruption of T cell homeostasis, a complete understanding of the mechanisms of CD4 + T cell decline remains elusive [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. Cytokines that signal through the common gamma chain, such as IL-2, IL-4, IL-7, and IL-15, are some of the main mediators of T cell homeostasis [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of HIV-infected South Africans also suggested that microbial translocation might be a driving force of chronic inflammation. 5 Monocyte activity might play a major role in the cases of microbial translocation-induced immune activation. 5 It was reported that the level of monocyte turnover was more pronounced than the viral load and lymphocyte activation in SIVinfected rhesus macaques; this finding implied that monocytes may be very important in the pathogenesis of AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…5 Monocyte activity might play a major role in the cases of microbial translocation-induced immune activation. 5 It was reported that the level of monocyte turnover was more pronounced than the viral load and lymphocyte activation in SIVinfected rhesus macaques; this finding implied that monocytes may be very important in the pathogenesis of AIDS. As a result of high TLR4 and CD14 expression, monocytes in the plasma of HIV patients were sensitive to high levels of LPS and inflammatory cytokines; 17 this result implied that the role of LPS is important in the pathogenesis of AIDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation